Traqueostomía en el paciente crítico - Romero P., Carlos; Cornejo R., Rodrigo; Tobar A., Eduardo; Llanos V., Osvaldo; Gálvez A., Ricardo; Espinosa N., María Angélica; Ruiz C., Mauricio (Revista Hospital Clínico Universidad de Chile, 2009)
Tracheostomy has evolved from a complex surgical intervention traditionally performed in the operating room, to a bedside procedure that can be done in the Intensive Care Unit, through a percutaneous approach. Percutaneous tracheostomy has proven to be as safe as open surgical tracheostomy in critically ill patients undergoing mechanical ventilation; therefore it seems to be a more suitable approach for these patients because it avoids the need of mobilizing patients outside their units and is performed in less time. Ciaglia Blue Rhino technique is the most widespread method of percutaneous dilatational tracheostomy, and exhibits an adequate safetyprofile. Fiberoptic bronchoscopy assistance and preliminary cervical ultrasound examination in selected patients improve the safeness of the procedure. Currently, the available evidence strongly suggests that achieving an early tracheostomy may shorten mechanical ventilation days and stay in the Intensive Care Unit, but a decline in ventilator-associated pneumonia incidence and overall mortality reduction remains to be proven. In hands of an experienced intensivist, relative contraindications should not be an impediment to perform a percutaneous tracheostomy, since it can be performed safely even in high risk critically ill patients. Recently completed studies and those close to be finished, will provide interesting data on this significant topic